anonymous
  • anonymous
Evaluate C - D. C=[7 11] [-15 3 ] D=[1 0] [4 -11/12]
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@oliviacaroline2123
anonymous
  • anonymous
@amistre64
Mehek14
  • Mehek14
|dw:1441556078271:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
i don’t get it
Mehek14
  • Mehek14
the first number for C at the top left is 7 the first number for D at the top left is 1 subtract 7-1 second letters at the top C = 11 D = 0 11 - 0 first number at the bottom C = -15 D = 4 2nd number at the bottom C = 3 D = -11/12 3 - (-11/12)
anonymous
  • anonymous
|dw:1441556260555:dw|
anonymous
  • anonymous
is that right?
Mehek14
  • Mehek14
7 - 1 = 6*
Mehek14
  • Mehek14
11 - 0 = 11 \(\checkmark\)
Mehek14
  • Mehek14
-15 - 4 = -19 \(\checkmark\)
Mehek14
  • Mehek14
now what about the last one?
anonymous
  • anonymous
how do i do the last one
Mehek14
  • Mehek14
3 - (-11/12) = 3 + 11/12 you can turn 3 into a fraction 3/1 = 36/12 \(\dfrac{36}{12}+\dfrac{11}{12}=\dfrac{47}{12}=3\dfrac{11}{12}\) or you can just put 3 before 11/12 = \(3\dfrac{11}{12}\)
anonymous
  • anonymous
i still don’t understand
Mehek14
  • Mehek14
just add 3 + 11/12 = \(3\dfrac{11}{12}\)
Mehek14
  • Mehek14
when you subtract by a negative, it becomes positive 3 - (-11/12) = 3 + 11/12 = 3 11/12
anonymous
  • anonymous
okay
anonymous
  • anonymous
now what do i do next
Mehek14
  • Mehek14
that's it
anonymous
  • anonymous
so those four answers are my answer?
Mehek14
  • Mehek14
|dw:1441556939428:dw|
anonymous
  • anonymous
okay thank you

Looking for something else?

Not the answer you are looking for? Search for more explanations.